Judicial use of episiotomy in singleton normal vaginal deliveries at term: the changing trend - Malik, Jyoti; Das, Sibadatta; Das, Ashima; Rai, Pinki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Episiotomy is the most commonly performed surgical procedures during delivery; but there is extensive disagreement about the necessity and benefits of this procedure. This study is an effort to compare the outcome of routine versus restricted use of episiotomy in tertiary care center. Methods: A prospective observational study was conducted for singleton normal vaginal term deliveries. Deliveries managed with routine use of episiotomy formed the ‘control group’, while those managed with restricted use of episiotomy formed the ‘study group’. Data so obtained was analyzed. Results: Total no of deliveries analyzed were 458 (210 control group+248 study group). Restricted use of episiotomy led to 64% (n=159) women delivering without any perineal lacerations in ‘study group’. This translated into 41% (n=38) reduction in no of perineal lacerations in primipara, and 23% (n=36) in multipara, compared to the ‘control group’. Only 2% of primipara in ‘study group’ had severe 3rd degree perineal tears. Conclusions: Restricted use of episiotomy resulted in considerable reduction in maternal morbidity due to perineal lacerations.